8 The Statutes at Large of Pennsylvania from 1682 to 1801, at 539 (1902) - (:unkn) unknown (My University, 1755)
Imposed a special tax on "every male white person capable of bearing arms, between the ages of sixteen and fifty years" who had not joined a militia.
Keywords: MILITIAS; TAX - MILITIAS